GLYX-13, a NMDA Receptor Glycine-Site Functional Partial Agonist, Attenuates Cerebral Ischemia Injury In Vivo and Vitro by Differential Modulations of NMDA Receptors Subunit Components at Different Post-Ischemia Stage in Mice - Zheng, Chen; Qiao, Zhi H.; Hou, Meng Z.; Liu, Nan N.; Fu, Bin; Ding, Ran; Li, Yuan Y.; Wei, Liang P.; Liu, Ai L.; Shen, Hui (Frontiers in Aging Neuroscience, 2017)
Excessive activation of NMDA receptors (NMDARs) is implicated in pathological form of plasticity named post-ischemic long-term potentiation (i-LTP) which was observed in glutamate mediated excitotoxity after stroke. In the past decades, many NMDARs inhibitors failed in clinical investigations due to severe psychotomimetic side effects. GLYX-13 is a NMDA receptor modulator with glycine site partial agonist properties and has potential protective effects on ischemic neuronal death. However, the underlying molecular mechanism of GLYX-13 attenuating the ischemic neuronal damage remains elusive. Our study was conducted to examine the molecular, cellular and behavioral actions of GLYX-13 in stroke, and further characterize the mechanism underlying the neuroprotective actions via modulation of the NMDAR subunit composition. In present study we found that in vitro OGD stroke model, GLYX-13 blocked i-LTP and restored the ratio of NR2A/NR2B subunit composition. The glycine site of NMDARs full coagonist D-serine completely blocked the effects of GLYX-13 on i-LTP. Besides, in vivo MCAO model, GLYX-13 decreased the cerebral infarct volume and reduced injury of hippocampus. Western analysis showed that GLYX-13 down-regulated the expression of phosphorylated NR2B (Tyr1472) and up-regulated phosphorylated NR2A (Tyr1325). Furthermore, GLYX-13 treatment along with NR2B specific antagonist (Ro256981) failed to exhibit any additional neuro-protective effects, whereas the application of NR2A antagonist (NVP-AAM007) abolished the neuroprotective effects of GLYX-13, which suggested that the protective action of GLYX-13 should be by its regulation of NMDAR subunit components. Our study provides important insights on the potential protective mechanism of GLYX-13 in ischemia and proposes the glycine site of NMDARs as a novel target for developing therapeutic strategies to store synaptic function in stroke.